New Activity of a Protein from Canavalia ensiformis - Vanya Petkova BOGOEVA; Lidiya Plamenova PETROVA; Anton Aleksandrov TRIFONOV (MDPI AG, 2014)
Concanavalin A is a legume lectin which preferentially agglutinates transformed cells and shows antitumor effects on human breast carcinoma cells in vitro and in vivo. It is considered as a new potential antineoplastic agent targeting apoptosis, autophagy, and anti-angiogenesis in preclinical or clinical trials for cancer therapeutics, which has recently become the object of intensive study. In the present investigation, we show the capacity of the lectin to bind manganese, gold, iron, and zinc porphyrins: all potential anticancer agents. The interaction of the legume lectin with the studied compounds has been investigated by tryptophan fluorescence, showing conformational changes within the quaternary and tertiary structures of the protein. The binding of Con A with manganese, gold, and iron porphyrins, as well as adenine, was studied by fluorescence quenching. In contrast, the interaction of Con A with zinc porphyrin caused an increase in Trp fluorescence and a red shift of 10 nm of the emission maximum position. However, the binding of Con A to iron porphyrin was accompanied by a 5 nm blue shift of the emission maximum, and a kD of 0.95 ± 0.13 μM was calculated, respectively. The sigmoidal shape of the curve showed cooperative interactions, which indicated the presence of more than one class of binding site within the Con A molecule for iron porphyrin, confirmed by the Hill slope (h = 1.89±0.46). We have found that the legume lectin interacts with porphyrins and adenine with an affinity (0.14-1.89 μM) similar to that of the non-legume lectin, wheat germ agglutinin. In conclusion, the protein Con A shows new binding activity towards porphyrins with anticancer activities and could find prospective application as a drug delivery molecule that specifically targets cancer cells.